The Role of Human Resources to Improve the Optimization of E-Procurement Implementation in PT Pertamina Trans Kontinental's Ship Operations - Musliha, Fadlia; Pahala, Yosi; Maemunah, Siti (Dinasti Publisher, 2025)
This study aims to analyze and evaluate the implementation of the e-procurement system in the operations of PT Pertamina Trans Kontinental (PT PTK) vessels, as well as the role of human resources (HR) in optimizing the application of this system. The research also explores the factors that influence the success of e-procurement implementation, both from the internal side of the company, such as good management and HR management, and from the external side, including supporting technological infrastructure and policies. This study uses a qualitative method with a descriptive approach and NVivo 12 software for data analysis. The research duration was 3 (three) months through interviews with informants consisting of the Procurement Manager, ICT Manager, Vessel Procurement and Operations Coordinator, SmartGEP Manager, and six HR employees involved in the implementation and management of the e-procurement system, totaling 10 participants, this research delves into the various challenges and solutions in implementing e-procurement in the vessel operations of PT PTK. The analysis results show that the implementation of e-procurement has increased efficiency, transparency, and accountability in the procurement of goods and services. However, there are still challenges related to HR adaptation and technological infrastructure. This research contributes to the development of e-procurement theory, particularly in the maritime industry context, and provides practical recommendations to enhance HR capacity in managing a more effective and sustainable e-procurement system.